2014
DOI: 10.1108/cwis-11-2013-0062
|View full text |Cite
|
Sign up to set email alerts
|

The use of social networking and learning management systems in English language teaching in higher education

Abstract: The use of web-enhanced teaching of the English as a foreign language in higher education in Greece is addressed in this case study which examines the student’s perceptions of online instruction using Moodle as a learning management system (LMS), with and without the use of Facebook (FB) as an adjunctive learning platform. The merging of this collaborative and interactive social platform with a LMS is explored, examining the attitudes of higher education foreign language learners toward Moodle as a LMS, and FB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 17 publications
4
40
1
1
Order By: Relevance
“…In this context, this finding is consistent with Lie (2013) that using online social network like Edmodo, students can improve their writing skills precisely through the process of giving response. In addition, the finding in general is also in compliance with Dogoriti et al (2014) showing the usefulness of social media as an adjunctive instructional tool which can facilitate the development of students' language skills, reinforced their cognitive skills and supported an active learning environment.…”
Section: Discussionmentioning
confidence: 63%
“…In this context, this finding is consistent with Lie (2013) that using online social network like Edmodo, students can improve their writing skills precisely through the process of giving response. In addition, the finding in general is also in compliance with Dogoriti et al (2014) showing the usefulness of social media as an adjunctive instructional tool which can facilitate the development of students' language skills, reinforced their cognitive skills and supported an active learning environment.…”
Section: Discussionmentioning
confidence: 63%
“…Other studies underlined that Facebook offers an alternative informal environment with flexible teaching and learning, and it increases students' interest and motivation (Dogoriti, Pange, & Anderson, ; Wichadee, ; Yen, Hou, & Chang, ). Compared with traditional LMS, Facebook appears to provide the opportunity to manage students' participation issues (Albayrak & Yildirim, ; Meishar‐Tal, Kurtz, & Pieterse, ) and to reduce obstacles like a lack of familiarity with LMS (Harmon, Alpert, & Histen, ).…”
Section: Formal Use Of Facebook In Formal Settings Of Learningmentioning
confidence: 99%
“…One final significant observation in the literature review is that both students and teachers made reference to the prospect of interaction SN offer (Aydın, 2017;Dogoriti et al, 2014;Razak et al, 2013). For instance, Aydın (2017) found that Turkish EFL students perceive Facebook as an environment for interaction, socialization, language learning and cultural encounters.…”
Section: Social Network In Second Language Learning Contextsmentioning
confidence: 99%